2020
DOI: 10.20527/jbk.v6i1.8356
|View full text |Cite
|
Sign up to set email alerts
|

Efektifitas Aromaterapi Lavender terhadap Tingkat Kecemasan Menghadapi Osce pada Mahasiswa Keperawatan

Abstract: Objective Structured Clinical Examintion (OSCE) merupakan salah satu metode penilaian kompetensi klinis. OSCE menimbulkan tekanan karena harus mengkolaborasikan skill dengan daya ingat yang kuat sehingga meningkatkan kecemasan yang akan berdampak pada perfoma mahasiswa. Salah satu bentuk strategi yang dapat digunakan untuk mengurangi kecemasan adalah dengan aromaterapi jenis lavender yang mempunyai sifat menenangkan, merangsang tidur, efek anxyolitic (anti kecemasan), dan efek psikologis lainya. Tujuan penelit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 4 publications
1
6
0
3
Order By: Relevance
“…Aromatherapy used in this study is lavender essential oil. Lavender is widely recommended for dealing with psychological problems because it contains linalool which has an anxyolytic or anti-anxiety effect (Harada et al, 2018;Setyawan & Oktavianto, 2020). This is consistent with the effect of lavender aromatherapy on anxiety reduction in coronary patients (Cho et al, 2013;Karadag et al, 2017) patients undergoing hemodialysis (Dehkordi et al, 2017) during labor (Mansour Lamadah, 2016) coronary artery bypass graft surgery patients (Rajai et al, 2016).…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Aromatherapy used in this study is lavender essential oil. Lavender is widely recommended for dealing with psychological problems because it contains linalool which has an anxyolytic or anti-anxiety effect (Harada et al, 2018;Setyawan & Oktavianto, 2020). This is consistent with the effect of lavender aromatherapy on anxiety reduction in coronary patients (Cho et al, 2013;Karadag et al, 2017) patients undergoing hemodialysis (Dehkordi et al, 2017) during labor (Mansour Lamadah, 2016) coronary artery bypass graft surgery patients (Rajai et al, 2016).…”
Section: Resultsmentioning
confidence: 59%
“…Lavender is an essential oil that has long been used to treat anxiety due to its calming, sleep-stimulating properties, anxiolytic (anti-anxiety) effects, and other psychological effects (Seifritz et al, 2019;Setyawan & Oktavianto, 2020;Zhang et al, 2016). Aromatherapy with lavender essential oil is expected to be one of the complementary therapies used to help patients relax and the hemodialysis process run smoothly.…”
Section: Introductionmentioning
confidence: 99%
“…Kelenjar pituitary juga menghasilkan endorphin sebagai neurotransmitter yang mempengaruhi suasana hati menjadi rileks. Meningkatnya enkephalin dan β endorphin akan membuat seseorang akan merasa lebih rileks dan nyaman (Setyawan & Oktavianto, 2020).…”
Section: Pengaruh Aromaterapi Jeruk Masam Terhadap Penurunan Nyeri Di...unclassified
“…Research by Setyawan and Oktavianto (2020) showed that giving lavender aromatherapy before the OSCE exam was proven to reduce anxiety in respondents. It is statistically proven that the mean TA score of the treatment group is significantly lower than the control group (p-value < 0.05).…”
Section: The Effectiveness Of Lavender Aromatherapy In Reducing Stude...mentioning
confidence: 99%
“…One type of aromatherapy that can be used to reduce anxiety is lavender. Lavender oil has been used since ancient times as a type of treatment because of its strong properties against relaxation, sedation, stress relief, calming the mind, and other psychological effects (Setyawan & Oktavianto, 2020).…”
Section: Introductionmentioning
confidence: 99%